An insider's guide to the UN - Fasulo, Linda M. (Yale University Press, 2004)
The United Nations increasingly finds itself at the centre of world events in an age of rapid globalization. It is therefore imperative that we understand its structure and functions. In this volume, news correspondent Lina Fasulo at the UN provides an introduction to its activities and goals. She draws on her own observations as well as on the insights of other individuals who have been active in the UN, including US ambassadors Richard Holbrooke, Madeleine Albright and John Negroponte. She explains how the UN came into existence, what governing principles guide its operation and what it is like to be a participant. She describes the organization, responsibilities and often tense politics of the Security Council. Surveying the many humanitarian, crime-fighting and peacekeeping programmes of the UN, Fasulo concludes that there are important reasons for Americans to give the United Nations their support.